2012
DOI: 10.1111/j.1747-6593.2012.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the effects of combining sewer junction characteristics on the hydraulic parameters of flow in fully surcharged condition

Abstract: In this study, the effects of different parameters on flow structure and flow hydraulics for combining sewer junction consisting of manhole and lateral inflow were investigated numerically. For this purpose, the effects of dimension variations, main and lateral pipe slope, angle and the joint position of lateral pipe beside manhole, manhole geometry, and the outflow rate of manhole on flow structure and energy loss coefficients were investigated. Results show that the rate of energy loss decreases by heighteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Saiyudthong [49] concluded that the surface simulation technique has a minor influence on energy loss coefficients when the manhole is highly surcharged. Zhao et al [26] and Motlagh et al [13] performed numerical simulations for rectangular and circular manholes, in which they used the VOF method to define the surface shape and location. Besides the surface properties, they also calculated the energy loss coefficients from the CFD results, compared them with the experimental results, and approved them.…”
Section: Numerical Model Procedures and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saiyudthong [49] concluded that the surface simulation technique has a minor influence on energy loss coefficients when the manhole is highly surcharged. Zhao et al [26] and Motlagh et al [13] performed numerical simulations for rectangular and circular manholes, in which they used the VOF method to define the surface shape and location. Besides the surface properties, they also calculated the energy loss coefficients from the CFD results, compared them with the experimental results, and approved them.…”
Section: Numerical Model Procedures and Boundary Conditionsmentioning
confidence: 99%
“…The inlet and outlet flow in different directions make the surface wavy and undulating, and vortex formations are observed in some regions of the manhole. Moreover, transitions between wholly and partially filled pipes are generally seen in the manhole regions [10,12,13]. Moreover, the complex nature of flow is affected by an almost infinite variety of geometrical and hydraulic factors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Motlagh et al investigated energy losses and flow behaviour in a more realistic model of a manhole with two inlet and one outlet pipe, reporting that increasing the height of the lateral inlet pipe causes energy loss coefficient to decrease as a result of decreasing eddy flow [5]. Chen et al performed a CFD analysis for optimization of a municipal sewer system design aiming to optimize the design of an existing combined sewer system and the numerical model was validated using experimental results [6].…”
Section: Introductionmentioning
confidence: 99%